Toxicity-guided assessment of disinfection by-products via machine learning and network toxicology - Jie Wang; Zhujun Liu; Ruipeng Lai; Xianyu Song; Yukun Zhang; Shuangliang Zhao; Honglai Liu (Water Research, 2026)

Structure-resolved adsorption of PFAS on humic substances: A combined study of molecular dynamics, explainable machine learning, and experiments - Yuxiang Nie; RuiPeng Lai; Huaicheng Bei; Xianyu Song; Dan Liu; Limeng Yin; Shuangliang Zhao; Honglai Liu (Chemical Engineering Journal, 2026)

Multi-compartmental Ni-MOF@C microcapsules for enhanced electrochemical detection of paracetamol and levofloxacin - Ruipeng Hao; Wanyu Xie; Danping Tian; Yifan Wang; Pei Zhang; Zheng Zhao; Xuwen Gao; Chen-zhong Li; Wenbo Lu (Analytica Chimica Acta, 2026)

Robust matching of SAR and optical images based on style consistency learning - Ruipeng Zhao; Penglin Zhang; Zhaoqian Wang; Wenfei Zhang; Yi Wan; Bin Zhang; Yongxiang Yao; Yongjun Zhang (International Journal of Remote Sensing, 2026)

Enhanced mechanical properties of concrete with 3D corrugated auxetic lattices - Yongpeng Lei; Ruipeng Liu; Xinjuan Zhao; Hui Wang (Engineering Structures, 2026)

Improved remediation mechanism of groundwater circulation wells based on ultrasonic permeability enhancement - Yan Zhao; Liu Yang; Siyuan Li; Mingxiu Ji; Ruipeng Dong (Process Safety and Environmental Protection, 2026)

Mechanism of direct-push injection impact on porous media structure and contaminant removal performance - Mingxiu Ji; Ruipeng Dong; Liu Yang; Shupei Wu; Yan Zhao (Journal of Contaminant Hydrology, 2026)

Defect-mediated permeation of deep eutectic solvents in cellulose crystals: A combined experimental and molecular dynamics study - Yuanhong Yu; Xianyu Song; Yanglong Wang; RuiPeng Lai; Yuxiang Nie; Wenjun Xiang; Chuxiang Zhou; Shuangliang Zhao; Honglai Liu (Carbohydrate Polymers, 2025)

Transforming residual biomass of Irish red seaweed Asparagopsis taxiformis and Palmaria palmata into biosorbents for methylene blue adsorption - Weihao Meng; Ruipeng Zhang; Siwei Gu; Ming Zhao; Jiani Luo; Colm P. O'Donnell; Yuan Li; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Algal Research, 2025)

Research on the in-situ permeability enhancement mechanism of loose porous medium using ultrasonic waves based on NMR - Yan Zhao; Liu Yang; Siyuan Li; Shengke Yang; Zhenkun Geng; Mingxiu Ji; Ruipeng Dong; Yinyu Wen (Journal of Hydrology, 2025)

Nickel isotopic variations in Ni–Cu sulfide deposits: from theoretical predictions to natural observations - Zhuang Ma; Shui-Jiong Wang; Wenzhong Wang; Matthew J. Brzozowski; Yun Zhao; Shengchao Xue; Ruipeng Li; Shangguo Su; Jie Yang (Geochimica et Cosmochimica Acta, 2025)

Identification of epiberberine from Scutellaria baicalensis as a selective TNF-α blocker for rheumatoid arthritis treatment - Zhiwei Zhang; Jingying Zhao; Guohao Zhang; Yi Feng; Pengcui Li; Xiaochun Wei; Li Guo; Ruipeng Zhao (Natural Product Research, 2025)

Correction to: Long noncoding RNA XIST inhibition promotes Leydig cell apoptosis by acting as a competing endogenous RNA for microRNA‑145a‑5p that targets SIRT1 in late‑onset hypogonadism - Jing Wang; Yiqiong Yang; Yang Xu; Zhipeng Xu; Xiaozhi Zhao; Ruipeng Jia; Yutian Dai (Cell and Tissue Research, 2025)

Effects of combined enzyme-alkali treatment on swelling ratio and texture of bovine omasal laminae - Jixing Yin; Shuangxi Guo; Yuwei Xia; Ruipeng Li; Jing Zhao; Junlong Bi; Wenbin Zhang (Food Chemistry, 2025)

December 2022 north American bomb cyclone: Insights from perturbation energetics - Emerson DeLarme; Jianping Li; Hongyuan Zhao; Yuan Liu; Ruipeng Sun (Atmospheric Research, 2025)

Cyclic behavior of rubber-coated stud-UHPC shear connectors exposed to reversed cyclic loadings - Shaodi Wang; Yuanhai Li; Ruipeng Wang; Yuhong Ma; Guifeng Zhao; Tianjun Zhang; Dawen Guo (Engineering Structures, 2024)

Enhancing deterministic prediction in unidirectional ocean waves using an Artificial Neural Network with exponential linear unit - Zhongying Feng; Zhan Wang; Kun Zheng; Ruipeng Li; Yuxin Zhao; Ye Wang (Ocean Engineering, 2024)

Long noncoding RNA XIST inhibition promotes Leydig cell apoptosis by acting as a competing endogenous RNA for microRNA-145a-5p that targets SIRT1 in late-onset hypogonadism - Jing Wang; Yiqiong Yang; Yang Xu; Zhipeng Xu; Xiaozhi Zhao; Ruipeng Jia; Yutian Dai (Cell and Tissue Research, 2024)

How does geopolitical risk affect carbon emissions?: An empirical study from the perspective of mineral resources extraction in OECD countries - Tao Ding; Hao Li; Ruipeng Tan; Xin Zhao (Resources Policy, 2023)

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Modeling health impacts of air pollutant emissions from the coal-fired power industry based on LCA and oriented by WTP: a case study - Ruipeng Tong; Yiran Wang; Xu Zhao; Xiaoyi Yang (Environmental Science and Pollution Research, 2022)

Effectiveness of road dust suppressants: insights from particulate matter-related health damage - Boling Zhang; Yiran Wang; Xu Zhao; Lanxin Cao; Ruipeng Tong (Environmental Geochemistry and Health, 2021)

Dynamic Response of Phragmites australis and Suaeda salsa to Climate Change in the Liaohe Delta Wetland - Yushu Zhang; Wenying Yu; Ruipeng Ji; Yijun Zhao; Rui Feng; Qingyu Jia; Jinwen Wu (Journal of Meteorological Research, 2021)

Modeling Canopy Carbon and Water Fluxes Using a Multilayered Model over a Temperate Meadow in Inner Mongolia - Nina Chen; Anzhi Wang; Juan An; Yushu Zhang; Ruipeng Ji; Qingyu Jia; Ziqi Zhao; Dexin Guan (International Journal of Plant Production, 2020)
To incorporate canopy vertical structure in a process-based model over a temperate meadow, a multilayered model estimated canopy carbon flux ( F c ) and water flux ( LE ) was applied by comparing with eddy covariance measurements in Inner Mongolia, China. Simulations of diurnal, seasonal CO 2 and H 2 O fluxes and model sensitivity to parameters and variables were analyzed. The results showed that the model underestimated F c and LE by about 0.6% and 5.0%, respectively. It was able to simulate the diurnal and seasonal variation of F c and LE and performed well during the day and in the growing season, but poorly at night and early in the growing season. F c was more sensitive to the leaf nitrogen content distribution coefficient and maximum catalytic activity of Rubisco, whereas LE showed greater sensitivity to the stomatal conductance parameter a 1 , empirical coefficient of stomatal response to saturated vapor pressure difference V pds0 , and minimum stomatal conductance of CO 2 g sc0 . The response of F c to environmental factors was ranked as air CO 2 concentration ( C a ) > air temperature ( T a ) > photosynthetically active radiation (PAR) > soil water content ( θ sm ) > vapor pressure deficit (VPD) > wind speed ( u 0 ). The response of LE to environmental factors was ranked as T a > VPD > θ sm > PAR> C a > u 0 . The response of LE to vegetation characteristic parameters was greater than that of F c .